Dynamics Of the House Of Representatives In Adjusting Legislation Post Constitutional Court Decision No.90/PUU-XXI/2023 - Hamid Noor Yasin; Suparno Suparno (Journal of Social Science, 2024)
This research analyzes the constraints and challenges faced by the House of Representatives (DPR) in following up on the Constitutional Court's decision No. 90/PUU-XXI/2023, with a focus on political and administrative aspects. Through an in-depth study, this research identifies various obstacles, such as differences of opinion among factions, the influence of political coalitions, and external pressures from the public and urgent national issues. Furthermore, this research highlights the complexity of bureaucracy and the limitations of human resources that affect the effectiveness of the legislative process. To address these challenges, this study recommends strategies for improving the quality of human resources and strengthening bureaucratic processes through the restructuring of procedures and the application of technology. The findings of this research are expected to provide valuable insights for the DPR in enhancing accountability and responsiveness to the needs of the public